THE ROLE OF LAW IN COMBATING THE SPREAD OF DEEPFAKE CONTENT FOR DIGITAL IDENTITY FRAUD - Lona Puspita; Sulton Firdaus, Hazmin (UIR Law Review, 2025)
Currently, in the process of developing artificial intelligence technology, a Deepfake phenomenon has emerged, namely technology that is capable of manipulating images, sounds, and videos realistically so that it will be difficult to distinguish from the original content. Although in the development of artificial intelligence technology it has the potential for positive use, such as in the world of entertainment and education, Deepfake can also pose a major risk in the current technological era, especially in terms of digital identity fraud. With the development of artificial intelligence technology, a new serious problem has arisen, one of which is the misuse of Deepfake which is part of artificial intelligence. The method used in this study is the normative legal research method with the main data source being secondary legal materials consisting of laws and regulations as well as reference books and journals. The results of the study state that the ambiguity of regulations can create legal loopholes that have the potential to be exploited by criminals, while the law enforcement process is hampered by the lack of clear guidelines, adequate tools and human resources. Therefore, strategic and systematic steps are needed to update the legal framework and cross-sector collaboration is needed.